The Effect of Corn Starch Substitution with Sargassum sp. Starch in Diet on Grow-Out of Cultivated Rabbitfish, (Siganus guttatus) in Floating Net Cages - Edison Saade; Usman Usman; Haura Ainun Sulaeman; Nursun Marhumatul Jannah (Journal of Aquaculture and Fish Health, 2022)
Corn starch is a source of carbohydrates for most cultivated fish, includes rabbitfish as one of the herbivores with high economic value. Therefore, rabbitfish requires cheaper carbohydrate sources to have a profitable business in its cultivation. This study was aimed to determine the substitution of corn starch with Sargassum sp. starch in the diet on the growth, relative feed intake, FCR and nutrient retention of rabbitfish. The average weight of rabbitfish used was 51.76±0.12 g/fish. Rabbitfish were cultivated in small net cages (1x1x1.5m) with a stocking density of 20 fish/net cage for 90 days reared. This study used an experimental method with a Completely Randomized Design (CRD). Corn starch (CM) substitution with Sargassum sp. starch (SM) by 0% (A), 21% (B), 42% (C), 63% (D) and 83% (E) used as the treatments with three replicates each. The measured parameters were weight gain (WG), relative growth (RG), relative feed intake (RFI), feed conversion ratio (FCR), protein retention (PR), energy retention (ER), and condition factor (CF). Data were analyzed using the analysis of variance (ANOVA) and Tuckey’s test. The results showed that the lowest FCR in treatment A had no significant effect with treatment B but was significantly different from treatments C, D and E. The WG, RG, RP and CF parameters had the same values at all levels of CM substitution with SM, while RFI and FCR increased with the increasing CM substitution by SM. It also indicated that CM in the rabbitfish diet could be substituted with SM by 83%.